(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigated the correlation between home numeracy experiences and numeracy skills development of 44 preschoolers enrolled at the Leyte Normal University Integrated Laboratory School (LNU-ILS) in School Year 2024-2025. Data on the preschoolers’ level of exposure to home numeracy experiences were collected from 44 parent-respondents using a Likert-type survey questionnaire which rated their exposure level as very high, high, or low. The level of the kindergarten pupils’ numeracy skills was determined by the kindergarten teacher-in-charge through the use of the Kindergarten Numeracy Checklist developed by the Department of Education. The study sought to identify specific home numeracy practices that significantly impact preschoolers’ numeracy skills, with the ultimate goal of developing an intervention plan to enhance numeracy learning both at home and in the classroom. The results of the study showed that at least four-fifths of the preschoolers in the study were already at the Advanced Level. While this is noteworthy, the task of bringing up the rest from the Intermediate and Beginner levels remains. The preschoolers surveyed had a generally high level of exposure to home numeracy experiences. They had very high exposure to numeracy skills, high exposure to number books, but low exposure to both games and application, indicating that the level of exposure to the last two components could still be improved. A statistical test for correlation indicated a significant relationship between the preschoolers’ exposure to home numeracy experiences and their numeracy skills. On the basis of the above-mentioned findings, this researcher has proposed a numeracy skills strategic intervention plan – it is a master plan that schools can adapt according to their specific needs to further enhance the numeracy skills development of their preschoolers.